Maternal under-nutrition and anaemia factors associated with low birth weight babies in Yemen - Muftah, Salem (International Journal Of Community Medicine And Public Health, 2016)
Background: Low birth weight is one of the main contributors to very high infant and under-five mortality rates in developing countries. The study aimed to identify the predicting risk factors for LBW in Yemen. Methods: An institutional-based, cross-sectional study was conducted from September 2014 to March 2015 and September 2015 to January 2016. Study procedures have included completing a questionnaire, maternal measurement of mid upper arm circumference, testing for haemoglobin level in mothers and weighing all targeted neonates. Descriptive, cross tabling and binary logistic regression analyses were used. Results: A total of 585 mother-neonate pairs were interviewed and examined for LBW and the associated risk factors. Logistic regression analysis identified three significant independent predicting factors; maternal under-nutrition (odds ratio (OR) 11.4, 95% CI 3.8 - 35.2), maternal anemia (OR 5.3, 95% CI 1.5 - 18.6) and rural residents (OR 0.2, 95% CI 0.1 - 0.7). Conclusions: Incidence of LBW in these communities was high. Maternal under-nutrition, maternal anaemia and rural settlements were significantly associated with babies with low weight at birth. There is a need for continued focus on maternal nutrition at the time of conception and during pregnancy both for the optimum feto-maternal health and national development.